P‐40: Glass substrate charging in flat panel display manufacturing. Issue 1 (25th September 2020) - Manley, Robert G.; Smith, Nicholas J.; Zhelev, Nikolay; Bhattacharyya, Indrani; Thelen, Dean; Streltsova, Elena; Walczak, Wanda; Mis, Jonathan; Agnello, Gabriel
Abstract : As technology in the arena of flat panel display progresses, panels are becoming larger, with higher pixel density and smaller device geometries. The glass sheets utilized in said panel fabrication processes are getting larger in area with Gen 10.5 (2940 mm × 3370 mm × 0.5 mm) sheets currently in mass production. With the increase in glass substrate size and decrease in the dimensions of devices fabricated on them, the continued trend will be towards greater sensitivity to electrostatic charge and possible failure. In this discussion, the role of glass charging in FPD manufacturing is presented, and its characterization is discussed.